The Impact of Social Media on The Voting Trend of Malaysian Undergraduates - Chang Yeow, Teng; Pandian, Sivamurugan; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2024)
Social media has had a significant impact on political communication and election outcomes worldwide. In Malaysia, politicians and parties have rapidly adopted social media platforms to engage with the electorate, highlighting its importance in shaping voter behavior and political campaigns. However, there is limited research on its specific impact on election outcomes. This study aims to examine how social media influences the decision-making of Malaysian undergraduates, who represent a significant portion of new voters due to the Undi18 initiative. This study utilized a multiple-choice questionnaire to gather data on the political preferences and behaviors of Malaysian undergraduates in the context of recent electoral changes. The questionnaire was distributed via the WhatsApp platform to ensure wide accessibility and participation among students across the country. The survey was conducted from January 17 to January 26, 2023, and received responses from 772 undergraduates enrolled in both public and private universities.The study reveals that platforms like TikTok play a crucial role in shaping political preferences and engagement among young voters. TikTok has become the primary source of information for this demographic, surpassing traditional media platforms like Facebook and television. The study also shows that social media influences go beyond information dissemination, impacting perceptions of political leaders and parties. Political parties are adapting to this shift by prioritizing platforms like TikTok for their campaigns, recognizing the importance of effective social media utilization for electoral success. Understanding the role of social media in shaping the political landscape is crucial for Malaysia's political future and for fostering a vibrant and inclusive democracy. The findings highlight the need for political parties to adapt to this new reality by engaging with young voters through innovative digital strategies and addressing their priorities transparently and accountably.